Disseminated tuberculosis presenting as medium‐vessel vasculitis in an immunocompromised host. (19th March 2020) - Wang, Jennifer Y.; Brown, Ryanne A.; Pugliese, Silvina; Kwong, Bernice Y.; Novoa, Roberto A.
Abstract: Cutaneous tuberculosis is an uncommon entity with several clinical forms recognized. Histopathologically, most cases are characterized by granulomatous inflammation and caseating necrosis, although less common findings, including vasculitis, have also been described. We report a 55‐year‐old male with a history of recently diagnosed dermatomyositis receiving immunosuppression with mycophenolate mofetil and prednisone, who developed multifocal soft tissue abscesses and an indurated erythematous plaque on the back. Skin biopsy of the back revealed a necrotizing medium‐vessel vasculitis. Mycobacterium tuberculosis was detected in the skin via acid‐fast bacilli stain and confirmed by tissue culture and polymerase chain reaction. Cutaneous findings improved rapidly with antituberculosis therapy. This case illustrates an uncommon clinical and histopathologic presentation of disseminated tuberculosis.